Nutritional profiling of Indian potato cultivars - Raigond, Pinky; Singh, Brajesh; Dutt, Som; Changan, Sushil S; Lal, Milan Kumar; Chaudhary, Dharmendra (Indian Horticulture, 2020)
Food security in broader way may be realized when all people at all the times have access to sufficient, safe, nutritious food to maintain a healthy and active life. Food security depends on availability of food, affordability and proper utilization of food. Potato (Solanum tuberosum) locally called as ‘aloo’ is one such candidate that can solve the problem of food security as well as malnutrition. Potato was accepted as a primary vegetable supplement because of its mild flavour and its utilization in combination with other foods. Nutritional value of potato was known since long, specially its high content of ascorbic acid to prevent scurvy. One of the prominent publications of the Food and Agriculture Organization (FAO 2008) has emphatically considered and recommended potato as a potential crop for the poorest of the poor, to ensure global food, nutritional and income security in future.